Answer: (4, -9)
<u>Step-by-step explanation:</u>
Use elimination method. Manipulate one (or both) equations to eliminate one of the variables and solve for the remaining variable. <em>I will be eliminating y</em>
6x + y = 15 → 2(6x + y = 15) → 12x + 2y = 30
-7x - 2y = -10 → 1(-7x + 2y = -10) → <u> -7x - 2y = -10</u>
5x = 20
x = 4
Next, replace "x" with "4" into either equation and solve for y.
6(4) + y = 15
24 + y = 15
y = -9
<u>Check:</u>
Plug in x = 4 and y = -9 into the other equation to verify it makes a true statement.
-7x - 2y = -10
-7(4) - 2(-9) = -10
-28 - -18 = -10
-28 + 18 = -10
-10 = -10 
Answer:
7, -1
Step-by-step explanation:
x^2 - 6x + 7 = 0
(x - 7)(x + 1) = 0
==> x = 7, x = -1
Average speed is given by [Total Distance] ÷ [Total Time]
Average speed =

km/hour
Hey there :)
( a - b )( a² + ab + b² )
Let us distribute ( a - b ) into the other
a ( a² ) + a ( ab ) + a ( b² ) - b ( a² ) - b ( ab ) - b ( b² )
a³ + a²b + ab² - a²b - ab² - b³
We can further simplify
a²b - ab² = 0
ab² - ab² = 0
a³ - b³You can see in the picture which I have attached. It is the 8th formula
30 is 20% of 150. Hope this pic helps